Botanical gestures and aesthetic experiences in educational research: disruptive inquirí laboratory (Praxis Educativa, 2024)
The article conceptualizes the category 'botanical gestures' and develops arguments about the relevance of its incorporation in educational research. This foundation includes a vast bibliographical tour through theoretical and literary texts. He also proposes two intermezzos that incorporate references to the visual arts. Finally, it states a propositional agenda that constitutes an expansion of two agendas previously stated by the authors of the work
Keywords: narrative research; education; botanical gestures; aesthetic experience; narrative research; education; botanical gestures; aesthetic experience